1999
DOI: 10.1046/j.1523-1739.1999.97300.x
|View full text |Cite
|
Sign up to set email alerts
|

Large Mammalian Herbivores and the Conservation of Arid Acacia Stands in the Middle East

Abstract: High mortality and poor recruitment in Acacia tree populations in many parts of the Middle East may result in loss of biodiversity. Human activities in recent decades have caused drastic changes in the water regime and the abundance of wild and domestic ungulates, which may negatively affect these trees. We studied the effects of large mammalian herbivores on the establishment of young Acacia raddiana and A. tortilis in the Arava Valley between the Red Sea and the Dead Sea, Israel. Seed accumulation under tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
124
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(133 citation statements)
references
References 25 publications
5
124
2
1
Order By: Relevance
“…In this case, the seeds may remain in the pod until they are eaten, infested, trodden on, or degraded by fungal attack [24] . According to Rohner and Ward [11] , infestation level in A. tortilis did not differ due to whether the pod on the tree or in the ground. Infestation level of A. tortilis was described to be 99% [25] , 96.2% [11] .…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…In this case, the seeds may remain in the pod until they are eaten, infested, trodden on, or degraded by fungal attack [24] . According to Rohner and Ward [11] , infestation level in A. tortilis did not differ due to whether the pod on the tree or in the ground. Infestation level of A. tortilis was described to be 99% [25] , 96.2% [11] .…”
Section: Resultsmentioning
confidence: 89%
“…Different studies showed contrasting effects of bruchid infestation on seed germination. Rohner and Ward [11] found a lower germination percentage for infested Acacia raddiana seeds (2.1%) versus 15.6% for intact seeds, while Miller [27] found insignificant differences in germination percentage between infested (2.5%) and intact (1.5%) seeds of A. tortilis. Mucungazi [5] found that bruchid beetles significantly reduced germination and seedling establishment of A. gerrardii, while they promoted germination of A. sieberiana.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…High browsing pressure over a longer period may also significantly retard growth, particularly in young trees (Martin and Moss 1997). Mammalian herbivores may, however, promote recruitment of Acacias in many ways (Rohner and Ward 1999;Or and Ward 2003).…”
Section: Introductionmentioning
confidence: 99%